The Church and the Armed Resistance Movement - Streikus, Arūnas (Genocidas ir rezistencija, 1997)
The post–war years were a difficult period of many trials for the Lithuanian people and social structures, including the Church. Lithuanian society at that time was strongly religiously committed and quite homogeneous from congregation point of view, and the influence of the Catholic Church on it was enormous. Thus, the Church’s relationship with the resistance movement was an important factor in the post–war historical processes in Lithuania. On the other hand, it was challenging to the Church itself, which had a significant impact on its further development under the Soviet totalitarian system. The aim of this presentation is to examine in more detail some aspects of this important post–war historical issue, without claiming it to be a comprehensive and exhaustive study. It will attempt to answer the following questions: what was the position of the hierarchs of the Lithuanian Catholic Church in relation to the armed resistance? What and how was it determined? How and why did it change? What was the reaction of the partisans to it? What is the relationship between the official position of the Church and the practices of ordinary clergy?
Keywords: Catholic Church; Soviet regime; armed resistance; bishops